Genotypes and Phenotypes of Enterococci Isolated From Broiler Chickens - Rehman, Muhammad Attiq; Yin, Xianhua; Zaheer, Rahat; Goji, Noriko; Amoako, Kingsley K.; McAllister, Tim; Pritchard, Jane; Topp, Edward; Diarra, Moussa S. (Frontiers in Sustainable Food Systems, 2018)
The objective of this study was to compare the resistance phenotypes to genotypes of enterococci from broiler and to evaluate the persistence and distribution of resistant genotypes in broiler fed bambermycin (BAM), penicillin (PEN), salinomycin (SAL), bacitracin (BAC) or a salinomycin/bacitracin combination (SALBAC) for 35 days. A total of 95 enterococci from cloacal (n=40), cecal (n=38) and litter collected on day 36 (n=17) samples were isolated weekly from day 7 to 36. All isolates were identified by API-20 Strep and their antimicrobial susceptibilities were evaluated using the Sensititre system with the commercially available NARMS’s plates of Gram positive bacteria. Whole genome sequencing (WGS) was used to assess their intra- and inter-genetic variability, with a focus on virulence and antibiotic resistance characteristics. All isolates were further characterized for hemolysin production (HEM), bile salt hydrolysis (BSH) and gelatinase (GEL) activities. Of the 95 isolates, E. faecium (n = 58) and E. faecalis (n = 24) were the most common Enterococcus species identified. Significant differences in the level of resistance for the E. faecium isolates to ciprofloxacin, macrolide, penicillin and tetracycline were observed among treatments. The bcrR, mefA and aac(6) genes were higher in BAM treatment than the other groups whereas bcrR, ermA, ermB, aphA(3) and tetL were more prevalent in PEN and BAC treatments. Overall, E. faecium isolates showed higher prevalence of antimicrobial resistance, but E. faecalis from litter also exhibited a significant level of resistance. A range of 4 to 15 different virulence genes was detected in E. faecalis. All isolates from litter but one (94.1%) showed BSH activities while 52.9% of them produced GEL. HEM activity was observed only in isolates collected on Day 7 (n= 9) and Day 14 (n= 1). This study confirmed that genetically diverse antimicrobial resistant enterococci harboring virulence factors can be promoted by the use of certain antimicrobials in feed and such enterococci could persist in broiler chickens and their litter, potentially contaminating the soil upon land application. This study underscores the need for ongoing monitoring the AMR enterococci.